Measures to Limit the offshore Use of Currencies : Pros and Cons. (IMF Working Papers; Working Paper ;, 2001)
Several Asian emerging market economies have recently adopted measures to limit the offshore trading of their currencies. This paper provides a general overview of such measures and evaluates the experiences of selected countries that resorted to such measures. It concludes that the measures could be effective if they were comprehensive and effectively enforced, and were accompanied by consistent macroeconomic policies and structural reforms. Such measures, however, could adversely affect investor confidence, financial market development, and nonspeculative economic and financial activities, and impose administrative burden on all parties involved.